Minimalisasi pemborosan menggunakan metode lean manufacturing dan green manufacturing di UKM. Asela - Chandrahadinata, Dody; Nur Fadilah, Rida (Institut Teknologi Garut, 2025)
This research aims to increase productivity by reducing waste through Lean Manufacturing and increasing profits through the utilization of raw materials in order to achieve a green manufacturing-based company. The calculation results of VALSAT Tools get a VA value of 65%, NVA 28% and NNVA of 6%. Based on the results of the weight of the 7 Waste questionnaire and 7 Waste Environmental, the biggest waste occurs in the waste of waiting by 42%, waste of transportation, inventory, and unnecessary motion by 17%. This research resulted in the design of Future Environmental Stream Mapping Design with a target cycle time of 5.94 hours from the initial time of 7.74 hours which increased productivity by 23%. And reducing solid waste from cutting fabric to make shoes resulted in a profit of Rp. 374,520. Improvement recommendations are given using the kaizen concept to reduce waiting time by reducing NVA and NNVA activity time so that it affects the production cycle time to be faster. 6R improvement recommendations are Reduce, Reuse, and Recycle to manage the waste generated.